Development of interventions to improve food handlers hand washing practices in selected school canteens in the Klang Valley, Malaysia - Ahmad, Izzah Az Zahra (2019)
In Malaysia, most of the reported cases of food poisoning occurred in public school canteen and because of that various efforts are made by Malaysian government to improve food safety practice in school canteen. However, despite the efforts the number of food poisoning cases still reported today. The food handlers in the institutional foodservice such as public school canteen must follow the proper food safety practice to prevent the outbreak of foodborne diseases. Addressing the hand washing practices is one way to improve food safety practices. It has been reported by prior studies that food handlers in Malaysia have low compliance rate of hand washing practices. And, there are lack of intervention studies to improve food handlers hand washing practices especially in Malaysia. Most of food safety intervention studies more focused on knowledge, although there are many possible factors beyond knowledge that affecting food safety practices. Therefore, the main objectives in this study is to develop hand washing intervention based on factors that affecting food handlers hand washing practices. Among others the objectives in this study is to elicit the beliefs of hand washing practices among food handlers and to identify specific factors that influence their hand washing practices. To achieve the objectives, this study employed mixed-methods approach which involved phase one and phase two. In the Phase One, a series of seven focus group discussions were held with food handlers from school canteen to assess food handlers’ beliefs on the hand washing practices at their workplace. The guide questions based on The Theory of Planned Behavior was employed during focus group discussion and the themes emerged were categorized according to the theory framework. Next, phase two involved survey and development of intervention. Findings from focus group discussion were used in survey instrument development. Then, a survey was conducted with 83 food handlers from public school canteen. The PLS-SEM analysed of survey revealed that only subjective norm significantly and positively predicts the food handlers’ intention to perform proper hand washing practices based on the path coefficient of 0.748 (p<.001). These suggests that food handlers’ subjective norms (e.g. manager, school administration, customer, co-worker, health officer) positively influence the food handlers hand washing practices. The development of intervention was continued afterward by incorporated the subjective norm factor and feedback performances was developed as main intervention with the integration of poster reminder and installation of soap and paper towel dispensers. The effectiveness of interventions was measured through the direct observation of food handlers hand washing practices in control group and intervention group during pre and post observation. The results of interventions do not significantly improve the hand washing compliance rate of food handlers. This could be due to various factors that affect interventions such as the way feedback performance were given, habit of food handlers and absent or lack of food safety culture in food handlers’ workplace. Although the implemented interventions do not improved hand washing compliance rate among food handlers, the finding still provides a valuable information to the management of school canteen, school administration and public authorities in their efforts to improved food safety practice in general and hand washing practices.